Differential expression of endoplasmic reticulum stress-response proteins in different renal tubule subtypes of OVE26 diabetic mice - Barati, Michelle T. (Cell Stress Chaperones, 2015)
Regulation of the endoplasmic reticulum (ER) stress-response pathway during the course of diabetes specifically in renal tubules is unclear. Since tubule cell dysfunction is critical to progression of diabetic nephropathy, this study analyzed markers of ER stress response and ER chaperones at different stages of diabetes and in different renal tubule subtypes of OVE26 type-1 diabetic mice. ER stress-response-induced chaperones GRP78, GRP94, and protein disulfide isomerase (PDI) were increased in isolated cortical tubules of older diabetic mice, while PDI was decreased in tubules of young diabetic mice. Immunofluorescence staining of kidneys from older mice showed GRP78 and PDI upregulation in all cortical tubule segments, with substantial induction of PDI in distal tubules. Protein kinase RNA-like endoplasmic reticulum kinase (PERK) phosphorylation was increased in cortical tubules of young diabetic mice, with no differences between older diabetic and control mice. Expression of ER stress-induced PERK inhibitor p58(IPK) was decreased and then increased in all tubule subtypes of young and older mice, respectively. Knockdown of PERK by small interfering RNA (siRNA) increased fibronectin secretion in cultured proximal tubule cells. Tubules of older diabetic mice had significantly more apoptotic cells, and ER stress-induced pro-apoptotic transcription factor C/EBP homologous protein (CHOP) was increased in proximal and distal tubules of diabetic mice and diabetic humans. CHOP induction in OVE26 mice was not altered by severity of proteinuria. Overexpression of CHOP in cultured proximal tubule cells increased expression of fibronectin. These findings demonstrate differential ER stress-response signaling in tubule subtypes of diabetic mice and implicate a role for PERK and CHOP in tubule cell matrix protein production.